Effect of Silicon Crystal Size on Photoluminescence Appearance in Porous Silicon. (15th June 2011) - Kumar, Pushpendra
Abstract : The photoluminescence (PL) study in porous silicon (PS) with decreasing Si crystallites size among the pores was reported. The PL appearance is attributed to electronic confinement in columnar-like (or dotlike) structures of porous silicon. Three different pore diameter PS samples were prepared by electrochemical etching in HF-based solutions. Changes in porous silicon and Si crystallite size were studied by observing an asymmetric broadening and shift of the optical silicon phonons in Raman scattering. Fourier transform infrared spectroscopy (FTIR) was used to study the role of siloxene or other molecular species, for example, SiH x in the luminescence mechanism. This mechanism was further studied by thermal annealing of PS at different temperatures. The PL of PS sample annealed at ≥300°C for 1 hr shows that trap electronic states appear in the energy gap of the smaller nano-crystal when Si–O–Si bonds are formed. From the observation of PL, Raman, and FTIR spectroscopy, the origin of PL in terms of intrinsic and extrinsic properties of nanocrystalline silicon was discussed.